Measuring Multisensory Integration in Clinical Settings: Comparing an Established Laboratory Method with a Novel Digital Health App - Valerie Nunez; James Gordon; Mooyeon Oh-Park; Jessica Silvers; Tanya Verghese; Vance Zemon; Jeannette R. Mahoney (Brain Sciences)
Background/Objectives: Recent research has correlated an inability to integrate sensory information with several adverse clinical outcomes, including slow gait, poor balance, and falls. For this reason, a digital health iPhone app (CatchU® v3.1.2) has been strategically designed to bring the measurement of visual–somatosensory integration into clinical settings. The purpose of this study was to determine whether CatchU could reliably capture the phenomenon of multisensory integration compared to a validated piece of laboratory apparatus (“tristimulator”). Methods: Using both the established tristimulator and CatchU, 50 participants (76.5 ± 6.2 years of age, 60% female) completed a simple reaction time test in response to visual, somatosensory, and combined visual–somatosensory stimulation. A reaction time cumulative distribution frequency (CDF) curve was calculated for each stimulus condition, and together these were used to calculate the CDF difference function (the multisensory visual–somatosensory CDF minus a magnitude-limited sum of the unisensory visual and somatosensory CDFs). From this, the magnitude of visual–somatosensory integration (VSI) was obtained. Results: CatchU captured multisensory integration in both average reaction times and the CDF difference function. It also produced a similar magnitude of VSI and showed no systematic bias compared to the laboratory stimulator. Additionally, CatchU responses were significantly less variable than responses recorded using the tristimulator. Conclusions: Despite using different forms of stimulation and different methods to record responses, these results reveal that CatchU can be used to produce the same inferences as laboratory apparatus. This confirms the ability of CatchU to reliably capture VSI.